Archaeological theory in a nutshell - Praetzellis, Adrian, 1952- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book provides a brief, readable introduction to archaeological theory. Adrian Praetzellis demystifies a pile of tricky contemporary concepts for the theory-phobic undergraduate or beginning graduate student. This new edition adds chapters on Indigenous, cognitive, and behavioral archaeologies and now covers 15 contemporary theories from neoevolutionism to queer theory. Each chapter begins with a description of the concept, its origin and significance. Next up is an example of how an archaeologist has used the idea to understand their site, making the connection between the idea and the archaeology plain and unambiguous. Each chapter ends with discussion questions and suggestions for further reading. A glossary of postmodern discourse (including that word) concludes the book. Using plain English to clarify some of the more baffling ideas used in contemporary archaeology, this book"--
How Theory Works -- Neoevolutionism -- Behavioral Archaeology -- Marxism -- Critical Theory -- Postcolonalism -- Indigenous Archaeology -- Feminism -- Queer Theory -- Structuralism -- Agency, Structure, and Structuration -- Transgressive Archaeologies -- Archaeological Biography -- Cognitive Archaeology -- Phenomenology -- Materiality and Thing Theory -- The Next Big Thing, or Where Do We Go From Here? -- Parlez-vous Po-Mo? A Mostly Postmodern Phrasebook.
Keywords: Archaeology -- Philosophy -- Textbooks; SOCIAL SCIENCE / Archaeology